Determination of psychological well being status among older persons in Northern Peninsular Malaysia - Momtaz, Yadollah Abolfathi; Yahaya, Nurizan; Tengku Abdul Hamid, Tengku Aizan (Indian Gerontological Association, 2009)
To determine the psychological well-being status and identify predictor variables significantly contribute towards the psychological well-being among older persons in Northern Peninsular Malaysia. A cross-sectional predictive correlational design was used for this study. The population comprised of 385 older persons with an average age of 69.3. Respondents completed a questionnaire booklet containing sociodemographic variables; self rated health, WHO-5 Well-Being Index, Intrinsic/Extrinsic-Revised Scale (I/E-R), Duke Social Support and Stress Scale and WHODAS II 12. The Statistical Package for Social Sciences (version 1 1.5) was used for data analysis. A total of 62.6 percent of elderly persons had good psychological well being status. Results of multiple regression analysis by enter method revealed that 46.3% of variance in psychological well being was explained by all predictor variables of the study. In addition, stepwise multiple regression analysis indicated seven significant predicting variables and measures namely physical health, disability, religiosity, social support, gender, housing quality, and employment status contributed to psychological well being. It is found that chronological age is not the cause of declining in psychological well being so psychological well being among older persons can be maintained and enhanced on condition that their social and physical needs are met well.